2008
DOI: 10.1134/s0006297908060011
|View full text |Cite
|
Sign up to set email alerts
|

Role of glyceraldehyde-3-phosphate dehydrogenase in vesicular transport from Golgi apparatus to endoplasmic reticulum

Abstract: Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) is a well-studied glycolytic protein with energy production as its implied occupation. It has established itself lately as a multifunctional protein. Recent studies have found GAPDH to be involved in a variety of nuclear and cytosolic pathways ranging from its role in apoptosis and regulation of gene expression to its involvement in regulation of Ca2+ influx from endoplasmic reticulum. Numerous studies also indicate that GAPDH interacts with microtubules and par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Among the identified proteins, we focused on one peculiar eukaryotic protein: the Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) annotated by spot number 49 on the 2D gel (Figure 2C) and in Table S1. GAPDH has multiple functions within host cells such as glycolysis and apoptosis [16],[17] More interestingly, GAPDH interacts with the small GTPase Rab 2 to control vesicular retrograde transport between the ER and the Golgi [18]. The presence of GAPDH on the BCV membrane leads us to hypothesise that vesicular retrograde transport may be involved in Brucella replication within the ER.…”
Section: Resultsmentioning
confidence: 99%
“…Among the identified proteins, we focused on one peculiar eukaryotic protein: the Glyceraldehyde-3-phosphate dehydrogenase (GAPDH) annotated by spot number 49 on the 2D gel (Figure 2C) and in Table S1. GAPDH has multiple functions within host cells such as glycolysis and apoptosis [16],[17] More interestingly, GAPDH interacts with the small GTPase Rab 2 to control vesicular retrograde transport between the ER and the Golgi [18]. The presence of GAPDH on the BCV membrane leads us to hypothesise that vesicular retrograde transport may be involved in Brucella replication within the ER.…”
Section: Resultsmentioning
confidence: 99%
“…This enzyme is also involved in vesicular transport from the Golgi apparatus to the endoplasmic reticulum (ER) [23], and has Ca 2+ -dependant fusogenic activity in human neutropil [105] and rat brain cytosol (Table 1) [106]. Previous studies demonstrated that fusogenic activity was dependent on Ser-234 [107], and inhibited by the substrate G3P.…”
Section: 0 Gapdh Functional Diversitymentioning
confidence: 99%
“…However, recent research suggests that GAPDH possesses highly diverse, non-glycolytic functions, as its expression and activity are affected by multiple factors. In particular, GAPDH has been reported to bind DNA and RNA[1, 46], regulate transcription [7], possess kinase/phosphotransferase activity [8–15], catalyze microtubule formation and polymerization [1622], facilitate vesicular transport [23], and bind integral membrane ion pumps associated with Ca 2+ release [24, 25], as well as interact with a number of small molecules, including tumor necrosis factor (TNF)-α ribozymes [26], glutathione (GSH) [27, 28], p53 [29–31], and nitric oxide (NO) [3234]. Additionally, since GAPDH also interacts with disease-associated proteins, like huntingtin [35] and the β-amyloid precursor protein (AβPP) [36].…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations have begun to illuminate these roles. These include endocytosis and membrane fusion, 17 translational control, 18 nuclear tRNA transport, 19 signaling, 20 pathogen virulence, 21 and cell death. 22 It is not clear how GAPDH can be targeted for these specific functions in the cell, but is believed to involve posttranslational modification of the protein.…”
Section: Introductionmentioning
confidence: 99%